ChemInform Abstract: High‐Performance Transition Metal‐Doped Pt3Ni Octahedra for Oxygen Reduction Reaction. Issue 36 (September 2015) - Mueller, T.; et al.
Abstract Pt3Ni octahedral nanoparticles supported on carbon black are prepared from solutions of Pt(acac)2 and Ni(acac)2 in DMF and benzoic acid as structure directing agent.